Šalutiniai pietų aukštaičių kirčiai - Leskauskaitė, Asta (Baltistica, 2002)
SECONDARY STRESS IN THE SOUTHERN AUKŠTAITISHDIALECT OF LITHUANIAN This paper sums up the empirical observations of the rhythmic, distinctive and non-distinctive secondary stresses in Southern Aukštaitish. The analysis has revealed the prevalence of the rhythmic stress and a mere optional use of the two other stresses. The occurrence and place of the stresses are conditioned by various factors: the syllabic structure of a word, the manner of speech (its tempo), the character of intonation, etc. The proof of the existence of the distinctive morpheme stress is based on the use of instrumental and auditory methods.